Produksi Tiga Varietas Kedelai Akibat Aplikasi Pupuk Hayati - Pieter, Yuniati; Mejaya, Made Jana (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
Soybean production at farmer level is still low, which ranges between 0.6-2.0 ton ha-1and average of 1.3 ton ha-1. Meanwhile, yield potential shows up to 3.0 ton ha-1. This big yield gap present an opportunity to increase yield through productivity approach, as well as other treatment including the use of inorganic and bio-fertilizers. An experimet has been executed to observe the production of 3 soybean varieties as affected by inorganic fertilizer and bio-fertilizer. The experiment was implemented at the Sugihan village, of the sub-district of Toroh, at Grobogan district, Central Java, in June â Sept 2014. The experiment was arranged in nested design with 2 factors, namely fertilization and variety, and in 3 replications. Three levels of fertilization were (1) Control (= Â½ Recommended dose, i.e.Urea (25 kg ha-1), SP-36 (50 kg ha-1), and KCl (50 kg ha-1), (2) Fertilizer A (= Control + F-1 Biofertilizer), and (3) Fertilizer B (=Control + commercial biofertilizer). Meanwhile, varieties of soybean used were Grobogan, Gema and Dering. The trials were implemented in 2 lands with different history, i.e. former land of rice plants that are subjected to site-specific nutrient fertilization (PHSL) and former land of rice plants with farmer treatment (Non-PHSL). The result showed that there is no significant difference caused by interaction between variety and fertilizer factors. Soybean variety was found to be main factor determining production level, while fertilizer treatment showed no significant effect on yield. The highest production (observed through square plot method) was found from Grobogan variety. Weight of 100 grain was identified as yield component with strongest correlation to soybean yield.Â